Strategi Pemasaran Madu Kele-Kele di Home Industri Bapak Yustika Desa Kuwum Kecamatan Mengwi Kabupaten Badung - Gregorius Ginting; Dian Tariningsih; Putu Fajar Kartika Lestari (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
The role of the agricultural sector in the national economy is very important and strategic. This is mainly because the agricultural sector still provides employment for the majority of the population in rural areas and provides food for the population. Another role of the agricultural sector is to provide raw materials for industry and produce foreign exchange through non-oil exports. Indonesia is very suitable for beekeeping business, because the country of Indonesia is very rich in a variety of flowering plants and agricultural products that can be used as a source of bee food, so it can be cultivated throughout the year. With the vast potential of forest resources in Indonesia, Indonesia has an advantage over other countries (Novandra, 2013). The purpose of this study is to identify and analyze internal factors that are the strengths and weaknesses of the Mdu Kele-Kele Home Industry. Identifying and analyzing external factors that pose opportunities and threats to the Honey Honey Home Industry, Identifying marketing strategies and marketing strategies that are appropriate for the Honey Honey Home Industry. The number of samples in this study were 12 respondents, the method of determining the sample with the population or census method. The analysis technique uses SWOT analysis. This study aimed to identify internal structural factors in home industry of honey that became strong was to maintain the quality of honey honey and promotion of honey honey. While internal factors that became a weakness were production not every not every day, promotion was still lacking, road towards the location is still damaged. Strati in marketing the home industry of the honey kele-kele by using the SWOT matrix. The strategy by using the power that takes advantage of opportunities is (SO) namely complete facilities then (ST) skilled management, (WO) Location far from the crowd, (WT) ) Lack of bee feed in the dry season.